Challenges and Development Strategy of Sharia Insurance in an Era of Economic Disruption - Syahputra, Angga; Nurtiyasari, Devi (EQUILIBRIUM, 2021)
The presence of Islamic insurance is an alternative to avoid conventional insurance, which is considered to have elements of usury, maytsir, gharar and zholim. In the era of economic disruption, Islamic insurance players and customers are waiting for the government's strategic policies as regulators and facilitators. The formulation of a sharia insurance development strategy policy begins with analyzing the obstacles to developing sharia insurance in Indonesia. These constraints mean that the number of sharia insurance customers in Indonesia is not maximal. These obstacles include the lack of socialization and promotion, inadequate use of technology, lack of product and service development, lack of knowledge, and the existence of conventional insurance. Based on these constraints, strategies for developing sharia insurance in Indonesia that can be carried out include maximizing socialization and promotion, maximizing the use of technology, developing products and services, increasing literacy, and market penetration. This research aims to analyze Islamic insurance's constraints and development strategies using a mathematical method, namely the Analytic Network Process (ANP) method so that scientific studies support policy recommendations. Furthermore, in this study, the ANP method was adopted in a survey design involving several respondents. The heterogeneity of the assessments of some respondents is expected to provide a more rational alternative. The analysis results using the ANP method are priority constraints to get more attention and priority strategies that can be used to formulate policies to make them more focused.